Expression of functionally active sialylated human erythropoietin in plants. Issue 3 (4th March 2013) - Jez, Jakub; Castilho, Alexandra; Grass, Josephine; Vorauer‐Uhl, Karola; Sterovsky, Thomas; Altmann, Friedrich; Steinkellner, Herta
Abstract Recombinant human erythropoietin (rhEPO), a glycohormone, is one of the leading biopharmaceutical products. The production of rhEPO is currently restricted to mammalian cell expression systems because of rhEPO's highly complex glycosylation pattern, which is a major determinant for drug‐efficacy. Here we evaluate the ability of plants to produce different glycoforms of rhEPO. cDNA constructs were delivered to Nicotiana benthamiana (N. benthamiana) and transiently expressed by a viral based expression system. Expression levels up to 85 mg rhEPO/kg fresh leaf material were achieved. Moreover, co‐expression of rhEPO with six mammalian genes required for in planta protein sialylation resulted in the synthesis of rhEPO decorated mainly with bisialylated N‐glycans (NaNa), the most abundant glycoform of circulating hEPO in patients with anemia. A newly established peptide tag (ELDKWA) fused to hEPO was particularly well‐suited for purification of the recombinant hormone based on immunoaffinity. Subsequent lectin chromatography allowed enrichment of exclusively sialylated rhEPO. All plant‐derived glycoforms exhibited high biological activity as determined by a cell‐based receptor‐binding assay. The generation of rhEPO carrying largely homogeneous glycosylation profiles (GnGnXF, GnGn, and NaNa) will facilitate further investigation of functionalities with potential implications for medical applications.